Electronic Medical Record–Assisted Telephone Follow-Up of Breast Cancer Survivors During the COVID-19 Pandemic: A Single Institution Experience. Issue 1 (22nd January 2021) - Merz, Valeria; Ferro, Antonella; Piras, Enrico Maria; Zanutto, Alberto; Caffo, Orazio; Messina, Carlo
Abstract : PURPOSE: The COVID-19 outbreak rapidly became a public health emergency and led to radical changes in patient management. From the start of the pandemic, we used electronic medical record–assisted telephone follow-up (E-TFU) of cancer survivors (CS) to minimize hospital exposure. The aim of this prospective study was to assess how breast cancer survivors (bCSs) perceived E-TFU. MATERIALS AND METHODS: A 15-item survey was e-mailed to bCSs who had been managed with E-TFU. The responses were measured using Likert-like scales and were correlated with the main characteristics of the bCS using Pearson's test. RESULTS: One hundred thirty-seven of 343 bCSs (40%) completed the survey between March 9 and June 2, 2020. Their median age was 59 years. Although 80.3% of bCSs were satisfied with E-TFU, only 43.8% would like to have E-TFU in the future. A low educational level was correlated with higher COVID-19–related anxiety ( P = .025). An older age ( P = .002) and a low educational level ( P < .0001) were correlated with the need to be accompanied to reach the hospital. A personal history of second cancer was inversely correlated with understanding medical advice ( P = .015) and the expectation of feeling relief after a follow-up visit ( P = .0027). Furthermore, pandemic phase II was correlated with satisfaction with E-TFU ( P = .010). CONCLUSION: E-TFU was an important means of avoiding hospital contacts during the COVID-19 pandemic, and the majority of bCSs in the survey were satisfied with this procedure. Further studies are needed to investigate the implementation of telemedicine even outside an emergency situation.